A review on genus Millettia: Traditional uses, phytochemicals and pharmacological activities - Rasmita Jena; Diptirani Rath; Sudhanshu Sekhar Rout; Durga Madhab Kar (Elsevier, 2020)
The genus Millettia belongs to Fabaceae includes 200 species which are distributed in tropical and subtropical regions of the world. Plants belong to this genus are used as folkloric medicine, for the treatment of different ailments like in wound healing, boil, sores, skin diseases, snake bite, muscle aches, pains, rheumatic arthritis, and gynaecological diseases. The aim of the review is to provide updated, comprehensive and categorized information on the aspects of ethnobotanical, phytochemical, pharmacological uses and toxicity of genus Millettia in order to identify their therapeutic potential and generate space for future research opportunities. The present study comprises of isolated flavonoids, phenolic compounds, phytosterols, saponins, alkaloids, polysaccharides, terpenoids and resins and pharmacological activities of various Millettia species. The relevant data were searched by using the keyword "Millettia" in different scientific databases like, "Google Scholar"; "NISCAIR repository"; "Pub Med"; "Science Direct"; "Scopus" and the taxonomy is validated by "The Plant List". This review discusses the existing information of the traditional evaluation as well as phytochemical and pharmacological evaluation of the extract and active constituents of the genus "Millettia". This review confirms that several Millettia species have emerged as a high-quality medicine in a traditional system for arthritis, wound healing, inflammation, skin diseases. Numerous conventional uses of Millettia species have been validated by modern pharmacology research. Intensive investigations of the genus Millettia relating to phytochemistry and pharmacology, especially their mechanism of action, safety, and efficacy could be the future research interests by the researcher in the area of phytomedicine.